Project Monitoring and Assessment System Design Using Rapid and Participatory Application Development Framework - Singgalen, Yerik Afrianto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This study investigates the implementation of Rapid and Participatory Application Development (RPAD) in educational settings, emphasizing its urgent necessity in enhancing project-based learning environments. Given the rapid pace of technological advancements and the evolving demands of modern education, there is an urgent need for innovative methodologies that can effectively integrate digital tools into the learning process. RPAD's iterative development process and active user involvement ensure the creation of functional and user-centric applications. The findings demonstrate that RPAD facilitates timely feedback, continuous improvement, and the effective integration of digital tools, enriching the learning experience and aligning theoretical knowledge with real-world applications. This methodology drives substantial improvements in teaching methodologies and student engagement and ensures that educational institutions remain adaptive and future-ready. The study concludes that adopting RPAD is crucial for enhancing the effectiveness and relevance of contemporary education, addressing current challenges, and preparing for future demands.